Remnant Cholesterol and Dyslipidemia Are Risk Factors for Guillain–Barré Syndrome and Severe Guillain–Barré Syndrome by Promoting Monocyte Activation - Ding, Yaowei; Wang, Lijuan; Sun, Jialu; Shi, Yijun; Li, Guoge; Luan, Xin; Zheng, Guanghui; Zhang, Guojun (Frontiers in Immunology, 2022)
Abstract Background: Guillain–Barré syndrome (GBS) is the most common severe acute paralytic neuropathy, with a mortality rate of 5% and permanent sequelae rate of 10%. Currently, the cause of GBS remains unclear. Therefore, we sought to determine potential predictors for GBS and its severity. Methods: A case–control study was performed at Tiantan Hospital in Beijing from January 2017 to December 2021. Laboratory and clinical characteristics were assessed in recruited GBS patients and healthy control individuals (matched by sex and age). The potential risk factors for GBS and severe GBS were assessed using a logistic regression analysis. The mRNA levels of toll-like receptor 4 (TLR4), toll-like receptor 2 (TLR2) and nuclear factor κB (NF-κB) in GBS patients and control PBMCs were detected by fluorescence quantitative PCR. THP-1 cells were costimulated with LPS and free cholesterol to demonstrate the effect of free cholesterol on monocyte activation. Results: A total of 147 GBS patients and 153 healthy individuals were included in the study. Logistic regression analyses showed that preceding infection, alcohol consumption, remnant cholesterol, homocysteine and the dyslipidemia index were correlated with a higher risk of GBS. In contrast, increased HDL cholesterol was correlated with a lower risk of GBS. Moreover, remnant cholesterol and the dyslipidemia index were significantly correlated with severe GBS. The mRNA levels of TLR4, TLR2 and NF-κB in the PBMCs of GBS patients were significantly higher than those of healthy individuals. LPS activated THP-1 cells, and free cholesterol treatment increased the expression of TLR4, TLR2, NF-κB and IL-1β mRNA in LPS-activated THP-1 cells. Conclusion: Dyslipidemia was correlated with the risk of GBS and severe GBS. Remnant cholesterol may promote the activation of monocytes in GBS patients. It may be valuable to control lipid levels in the prevention of GBS and severe GBS.